Smell of cells: Volatile profiling of stem- and non-stem cell proliferation. (1st March 2018) - Bischoff, Ann-Christin; Oertel, Peter; Sukul, Pritam; Rimmbach, Christian; David, Robert; Schubert, Jochen; Miekisch, Wolfram
Abstract: Bacterial and cell cultures are known to emit a large number of volatile organic compounds (VOCs). Conventional biochemical methods are often destructive, time-consuming and expensive. In contrast, VOC analysis of headspace over cultures may offer a non-destructive alternative for the monitoring of cell proliferation and metabolism. VOC profiles from cultures of murine pluripotent stem cells and fibroblasts were assessed every 24 h for 3 days. Pure cell media were measured as parallel controls. VOC analysis was highly standardized with respect to time of measurement and phases of cell growth. Cultures were grown in custom-made inert boxes. In order to determine the effects of fresh media supply on VOC emissions, both cell types were cultured with and without daily media exchange. VOCs from headspace were preconcentrated by means of needle trap micro-extraction and analysed by gas chromatography-mass spectrometry (GC-MS). Murine pluripotent stem cells emitted increasing concentrations of thiirane and methyl-methoxy-hydroxy-methyl-amine (MMHA). Substance concentration correlated with cell numbers. Murine fibroblasts did not emit thiirane or MMHA. Concentrations of aldehydes, especially benzaldehyde, were lower in both cell cultures than in pure media samples. Daily media exchange resulted in higher cell numbers, but had no major effects on VOC concentrations emitted from the cells. Investigation and monitoring of volatile substances such as thiirane and MMHA may enhance the understanding of stem cell properties and lead to a destruction-free characterization of pluripotent stem cells.